"Negotiating partnerships:" parents' experiences of collaboration in community mental health and substance use services. Issue 4 (21st November 2016) - Ness, Ottar; Borg, Marit; Semb, Randi; Topor, Alain
Abstract : Purpose: The importance of collaboration in the mental health field is a well established theoretical principle, but there has so far been less attention to its practical implications from a parents' perspective. The purpose of this paper is to describe parents' experiences of collaboration with mental health practitioners. Design/methodology/approach: This was a qualitative study based on thematic analysis of multi-stage focus group discussions with ten parents of young adults with co-occurring mental health and substance use problems. Findings: The authors identified three major themes related to family member's experiences of collaborative practices: negotiating partnerships, incomprehensible services and being the young adult's advocate. Research limitations/implications: A potential limitation of this study is that the parents who agreed to take part in this study were all part of the population who really want to be involved in their relative's care; other family members who did not take part may have different feelings. It would be interesting to interview the siblings and partners of young adults with mental health and substance abuse problems. A last limitation is that only family parents participated in these focus group discussions; it would be interesting to invite service users and practitioners to elicit information about similarities and differences in their experiences of collaborative practices. Practical implications: This study emphasises that parents should be seen as unique individuals as well as families. Parents are persons in different contexts. This creates different needs in their collaboration with the professionals. Parents want to be invited to contribute with their experiences and knowledge, being a collaborative partner in the service provision, and not a burden for their young adults, or to the professionals. Social implications: This study emphasises that it may be important to understand the complex situations of each family parent, supporting their loved ones and at the same time living lives of their own. Families are in demanding and stressful situations often over many years. They want to be invited to contribute with their experiences and knowledge, being a collaborative partner in the service provision, and not a burden for their young adults, or to the professionals. Originality/value: The importance of collaboration is well established in in the mental health field. However, there has been less attention to what collaboration with parents might involve in practice. This paper describes the collaborative experiences of parents of young adults (18-28 years) with co-occurring mental health and substance use problems.